EARLY DIAGNOSIS OF ANASTOMOTIC LEAKAGE AFTER ELECTIVE COLO-RECTAL SURGERY USING DUTCH LEAKAGE SCORE – A PROSPECTIVE OBSERVATIONAL STUDY - MOHANTY, SUJIT KUMAR; MOHANTY, SHUSHRUTA; SUKLA, ASHIS KUMAR; SAHOO, SANJAYA KUMAR; SAHOO, IPSITA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Anastomotic leakage is a major complication after colorectal surgery, with reported incidence of 2–7%. To limit the clinical consequences, it should be detected and treated as soon as possible. Leak usually becomes apparent between 5 and 7 days postoperatively. A standardized post-operative score, Dutch Leakage Score (DLS) can be a useful clinical tool to reduce delay in diagnosis of anastomotic leak (AL) and reduce mortality. A score of <4 was considered negative while a score of 4 or more was considered positive. Methods: Total 110 patients were enrolled after written informed consent during March 2021–October 2022 at a tertiary care hospital in Odisha. DLS was measured before surgery and on POD2, POD3, and POD6. Results: Among the 110 patients, the AL rate was 16.4%. With respect to AL, DLS cutoff of 2.5 on POD2 had positive predictive value (PPV) of 53.10% and a negative predictive value (NPV) of 98.70%. DLS cutoff of 4.0 on POD3 had a PPV of 80.90% and a NPV 98.90%. DLS cutoff of 3.0 on POD6 had a PPV of 84.20% and a NPV of 96.70%.The most common day of AL was the fifth P.O.D (in seven patients) followed by sixth P.O.D (in five patients). Conclusion: DLS is a good positive and excellent negative predictor of AL. DLS is an easy bedside assessment to gauge the likelihood of AL in the early post-operative period.